Antimicrobial activities of chicken β-defensin (4 and 10) peptides against pathogenic bacteria and fungi - Yacoub, Haitham A.; Elazzazy, Ahmed M.; Abuzinadah, Osama A. H.; Al-Hejin, Ahmed M.; Mahmoud, Maged M.; Harakeh, Steve M. (Frontiers in Cellular and Infection Microbiology, 2015)
Host Defense Peptides (HDPs) are small cationic peptides found in several organisms. They play a vital role in innate immunity response and immunomodulatory stimulation. This investigation was designed to study the antimicrobial activities of β-defensin peptide-4 (sAvBD-4) and 10 (sAvBD-4) derived from chickens against pathogenic organisms including bacteria and fungi. Ten bacterial strains and three fungal species were used in investigation. The results showed that the sAvBD-10 displayed a higher bactericidal potency against all the tested bacterial strains than that of sAvBD-4. The exhibited bactericidal activity was significant against almost the different bacterial strains at different peptide concentrations except for that of P. aeruginosa and Str. bovis strains where a moderate effect was noted. Both peptides were effective in the inactivation of fungal species tested yielding a killing rate of up to 95%. The results revealed that the synthetic peptides were resistant to salt at a concentration of 50mM NaCl. However, they lost antimicrobial potency when applied in the presence of high salt concentrations. Based on blood hemolysis studies, a little hemolytic effect was showed in the case of both peptides even when applied at high concentrations. The data obtained from this study indicated that synthetic avian peptides exhibit strong antibacterial and antifungal activity. In conclusion, future work and research should be tailored to a better understanding of the mechanisms of action of those peptides and their potential use in the pharmaceutical industry to help reduce the incidence and impact of infectious agent and be marketed as a naturally occurring antibiotic.